Tackling malnutrition - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Malnutrition, especially protein deficiency among children, continues to affect many rural areas in Malawi. Poverty, exacerbated by declining soil fertility, erosion and drought, has lead to many poor households being unable to meet their...